Different prelamin A forms accumulate in human fibroblasts: a study in experimental models and progeria - S Dominici; V Fiori; M Magnani; E Schena; C Capanni; D Camozzi; MR D’Apice; C Le Dour; M Auclair; M Caron; G Novelli; C Vigouroux; et al. (European Journal of Histochemistry, 2009)
Lamin A is a component of the nuclear lamina mutated in a group of human inherited disorders known as laminopathies. Among laminopathies, progeroid syndromes and lipodystrophies feature accumulation of prelamin A, the precursor protein which, in normal cells, undergoes a multi-step processing to yield mature lamin A. It is of utmost importance to characterize the prelamin A form accumulated in each laminopathy, since existing evidence shows that drugs acting on protein processing can improve some pathological aspects.We report that two antibodies raised against differently modified prelamin A peptides show a clear specificity to full-length prelamin A or carboxymethylated farnesylated prelamin A, respectively. Using these antibodies, we demonstrated that inhibition of the prelamin A endoprotease ZMPSTE24 mostly elicits accumulation of full-length prelamin A in its farnesylated form, while loss of the prelamin A cleavage site causes accumulation of carboxymethylated prelamin A in progeria cells. These results suggest a major role of ZMPSTE24 in the first prelamin A cleavage step.